Gavetos Curvos: um percurso pela habitação plurifamiliar portuense na primeira metade do século XX - Inês Maria Braga Oliveira (2018)
The present dissertation is developed in the sense of reflecting about the corner building: the building that inserts itself on the intersection of two front of streets. In order to find specific meanings and sources, the present reflection seeks to discover the approaches on the subject, as well as to analyze constructed examples. The Porto context and the housing program are, due to the adequacy and ease of study, the circumstance in recognition. According to a structure composed of three major themes - lot, composition and image - a study of forty-two examples is formed, where the curved form is the main selection criterion.